Neuroprotective potential of isofraxidin: Alleviating parkinsonian symptoms, inflammation and microglial activation - Tin-An Wang; Shiao-Yun Li; Li-Yun Fann; I-Hsun Li; Tsung-Ta Liu; Hao-Yuan Hung; Chieh-Wen Chang; Chih-Chien Cheng; Ying-Che Huang; Pei-Yeh Yu; Jui-Hu Shih (Journal of Central Nervous System Disease)
Background Parkinson’s disease (PD) is one of the most common neurodegenerative disorders. Previous research has confirmed that isofraxidin can reduce macrophage expression and inhibit peripheral inflammation. However, its effects on the central nervous system remain underexplored. Objective This study aims to determine whether isofraxidin offers protective effects against PD. Methods To assess the effects of isofraxidin, motor performance changes in LPS-induced PD mice were evaluated using rotarod, pole-climbing, and beam-walking tests. Striatal damage was examined through [ 18 F]fluorodeoxyglucose ([ 18 F]FDG) positron emission tomography (PET) imaging, and dopaminergic neurotoxicity was assessed using tyrosine hydroxylase (TH) staining. Microglial accumulation and activation were monitored with Iba-1 staining, while LPS-induced inflammation was examined via TNF-α and IL-1β staining. Results Isofraxidin pre-treatment significantly improved LPS-induced motor dysfunction, as evidenced by better performance in the rotarod, pole-climbing, and beam-walking tests. [ 18 F]FDG PET imaging showed that isofraxidin restored glucose uptake in the striatum, countering LPS-induced damage. Furthermore, Iba-1 staining revealed that isofraxidin markedly inhibited LPS-induced microglial activation and accumulation. TNF-α and IL-1β staining indicated a reduction in inflammation with isofraxidin treatment. Additionally, TH staining supported the neuroprotective role of isofraxidin on dopaminergic neurons. Conclusions Isofraxidin exhibits notable neuroprotective properties by mitigating LPS-induced parkinsonian behaviors, microglial activation, inflammation, and dopaminergic neuron damage. These results highlight isofraxidin’s potential as a therapeutic intervention for PD.